(untitled) (Northern International Medical College Journal, 2022)
Background : Globally incidence of Type 2 Diabetes Mellitus (T2DM) shows an upward trend which a challenge for physicians and public health specialists. Patients with T2DM have 2- 4-fold increased risk of coronary artery disease (CAD), the leading cause of death among people with T2DM. Dyslipidemia considered an important factor for cardiovascular complication of T2DM. Objective : Assessment of dyslipidemia and its association with T2DM in Bangladeshi subjects. Methods : A case control study was conducted in CARe Medical College Hospital, Dhaka, during the period of July 2018 to June 2019. A total 153 subjects were included in study of which 90 belonged to Group-I were T2DM and 63 subjects were healthy Controls in Group-II. The Fasting glucose, postprandial glucose. Serum Lipid Profile were assayed in patients and controls, using standardized assay methods. Data were analyzed by using SPSS version 21. Results : Fasting plasma glucose levels [mmol/l, (Mean± SD)] of the study group were Control (4.96 ± 0.76) and T2DM (8.27±2.19) difference was statistically significant (p <0.001), 2 hours post prandial plasma glucose level [mmol/l, (Mean± SD)] of the study groups were Control (5.81±0.87) and T2DM (11.79 ± 2.69). A significant difference found between Control vs T2DM (p <0.001). Fasting Triglyceride [mg/dl, (Mean± SD) was higher in T2DM (189±82.06), compared to Control (142±80.14) and statistically significant p=0.001. Total Cholesterol [mg/dl, (Mean± SD), Control (172±45) and T2DM (189±50.76) p=0.029] was significantly higher in T2DM than healthy subjects. HDL cholesterol [mg/dl, (Mean± SD); Control (30.6±8.10) and T2DM (26±9.94), p<0.001] significantly increased in healthy Controls compared to T2DM subjects. LDL cholesterol [kg/m,2 (Mean± SD); Control (114±43.54) and T2DM (118±49.66), p=0.572] which was not significantly different among the study subjects. Conclusion : The present study concludes that important parameter of dyslipidemia, Fasting Triglyceride, total Cholesterol, were higher in T2DM patients and statistically significant. LDL cholesterol higher and not significant on the other hand HDL cholesterol was lower but significant difference between T2DM and healthy control found. Therefore, T2DM is associated with higher incidence of dyslipidemia Northern International Medical College Journal Vol. 12 No.1 July 2020, Page 507-510